BIOMECHANICAL ASPECTS OF PERTHES DISEASE (MATHEMATICAL MODELING) - Fizor, V.D.; Korolkov, O.I.; Karpinsky, M.Yu.; Karpinska, O.D.; Yaresko, O.V. (World of Medicine and Biology, 2024)
A geometric model with muscles functionally related to the hip joint was created. We studied the effect of muscles on the vector of the net effect when changing the position of the limb: passive lifting and adduction. During passive hip flexion, stretching occurred in gracilis, adductor magnus, gluteus maximus, biceps femoris, semitendinosus, semimembranosus. The net force vector initially decreases, and at maximum bending it increases. When increasing the effort of muscles m. gluteus maximus – the angle of co-action is reduced, and m. gracilis, adductor magnus, biceps femoris, semitendinosus, semimembranosus –is increased. Adduction of the lower limb leads to passive stretching of the muscles: mm. rectus femoris, gluteus medius, gluteus minimus, tensor fascia latae, biceps femoris, semitendinosus, semimembranosus. The greatest elongation is determined in m. tensor fasciae latae, and the greatest efforts were found in m. gluteus medius. With simultaneous bending and adduction of the lower extremity, mm gracilis, adductor magnus, gluteus maximus, gluteus medius, tensor fasciate latae, biceps femoris, semitendinosus were subjected to passive stretching, which causes an even greater deviation of the resultant force vector from the normal than when the limb is flexed or adducted.